Developing a competence framework for nurses in pharmaceutical care: A Delphi study. (September 2021) - Dijkstra, Nienke E.; De Baetselier, Elyne; Dilles, Tinne; Van Rompaey, Bart; da Cunha Batalha, Luis M.; Filov, Izabela; Grøndahl, Vigdis Abrahamsen; Heczkova, Jana; Helgesen, Ann Karin; Jordan, Sue; Kafková, Zuzana; Karnjus, Igor; et al.
Abstract: Background: Nurses play an important role in pharmaceutical care. They are involved in: detecting clinical change; communicating/discussing pharmacotherapy with patients, their advocates, and other healthcare professionals; proposing and implementing medication-related interventions; and ensuring follow-up of patients and medication regimens. To date, a framework of nurses' competences on knowledge, skills, and attitudes as to interprofessional pharmaceutical care tasks is missing. Objectives: To reach agreement with experts about nurses' competences for tasks in interprofessional pharmaceutical care. Methods: A two-phase study starting with a scoping review followed by five Delphi rounds was performed. Competences extracted from the literature were assessed by an expert panel on relevance by using the RAND/UCLA method. The experts (n = 22) involved were healthcare professionals, nurse researchers, and educators from 14 European countries with a specific interest in nurses' roles in interprofessional pharmaceutical care. Descriptive statistics supported the data analysis. Results: The expert panel reached consensus on the relevance of 60 competences for 22 nursing tasks. Forty-one competences were related to 15 generic nursing tasks and 33 competences were related to seven specific nursing tasks. Conclusions: This study resulted in a competence framework for competency-based nurse education. Future research should focus on imbedding these competences in nurse education. A structured instrument should be developed to assess students' readiness to achieve competence in interprofessional pharmaceutical care in clinical practice.